Studi Jenis-Jenis Zingiberaceae di Kawasan Hutan Lindung Gunung Talang Sumatera Barat - Aulia Muhradi Delta; Ardinis Arbain; - Syamsuardi (Universitas Andalas, 2013)
Floristic study on Zingiberaceae at Protected Forest areas in Talang Mount, West Sumatra has been carried out from July 2012 to April 2013. Samples of Zingiberaceae were directly collected during tracking and searching along three exploration routes to top of mount Talang i.e. the Batu-Banjanjang, Aie Batumbuk and Koto Gadang Guguk. The samples were processed to herbariums specimen and identified at Herbarium Universitas Andalas (ANDA) Padang. Based on analysis of morphological characters, nine species of Zigiberaceae were identified; Etlingera elatior, Etlingera sp., Etlingera foetens, Geostachys sp., Globba aurantiaca, Globba talangensis, Hedychium coronarium, Hornstedtia Pininga and Zingiber zerumbet. We suggested further research for Etlingera sp. and Geostachys sp. on its possibility as new species.